Back-End development on Laboratory Information System in Universitas Riau - Muhammad Hakim Saputra; Rahmat Rizal Andhi; Edi Susilo (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2023)
Laboratories usually have different tools, materials, documents, and a lot of other content. At the University of Riau, especially the Faculty of Engineering, it is filled with many laboratories. Starting with a computer network laboratory and chemical laboratory, machine laboratory, and many more. Currently information about laboratories cannot be found on the internet, and it is still difficult to access information about laboratories. This research focuses on creating a back-end system that can later be implemented in the development of a laboratory information system. This development process uses the V-Shaped model as a reference in the manufacturing stages. The system that has been made will be tested using the unit testing, integration testing, and system testing methods with ISO 25010 as a reference standard in determining the quality of the tests carried out. The results of testing the system obtained very good results with A results on reliability, maintainability, and security testing. In testing the efficiency of the system in getting a response time 80ms average on each page. White box testing also obtained results that all the features and data in the system were functioning and matched as they should.